Defining ‘Architecture’ for Software Engineering – A Review of Terminology - Guzmán Benavides, Julio César (2017)
There are many terms used in the industry that relate to similar topics. Architecture is one of them. In many companies, representatives develop Information Architectures even though this term was conceptualized to be used in the domains of Information Systems or Information Technology. Moreover, different consultant agencies, consortia or working groups create standards or guidelines that sometimes use these concepts interchangeably. In this paper, we want to provide a comprehensible definition of the most common (Architecture-related) concepts used by members of the information technology community into non-software development companies. In addition, a literature review is also conducted to determine the academic use of these terms, and a website based review is conducted to gather the most common definitions provided in articles that do not undergo peer reviews.